(untitled) (diségno, 2017)
The UID Scientific Committee has granted its patronage and logo for the Study Days Fortified Architecture. Survey and Restoration which took place in March of 2016 in Bari, at the Department of Civil Engineering and Architecture (DICAR) of the Polytechnic University of Bari. On behalf of UID, I would like to thank everyone for the work done and for the valuable act of dissemination provided to the entire scientific community and particularly to the education of our young people, starting, for purposes of research or simply for related learning, to construct a knowledge base strongly rooted in a territory of architectural works built specifically as castles for the defense and protection of these places.